APPLICATION OF CREATIVE PEDAGOGY BASED ON MODERN DIDACTIC MODELS - Tulayeva Nafisa Majidovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article investigates the application of creative pedagogy within the context of Uzbekistan’s education system, specifically in relation to modern didactic models. As Uzbekistan reforms its national curriculum and teacher training programs to meet global standards, integrating creativity into pedagogical practices becomes imperative. This study combines theoretical analysis and empirical data from local schools, national education strategies, and international benchmarks such as PISA and OECD data. It reveals that the implementation of creative, learner-centered methods—when aligned with didactic models like project-based learning, flipped classrooms, and digital pedagogy—significantly enhances learning outcomes, student motivation, and adaptability. The findings provide policy recommendations for Uzbekistan’s education sector reform strategy for 2025–2030.